Divergent evolution in antiherbivore defences within species complexes at a single Amazonian site. (17th June 2015) - Endara, María‐José; Weinhold, Alexander; Cox, James E.; Wiggins, Natasha L.; Coley, Phyllis D.; Kursar, Thomas A.; Carson, Walter
Summary Classic theory in plant–insect interactions has linked herbivore pressure with diversification in plant species. We hypothesize that herbivores may exert divergent selection on defences, such that closely related plant species will be more different in defensive than in non‐defensive traits. We evaluated this hypothesis by investigating two clades of closely related plant species coexisting at a single site in the Peruvian Amazon: Inga capitata Desv. and Inga heterophylla Willd. species complexes. We compared how these lineages differ in the suite of chemical, biotic, phenological and developmental defences as compared to non‐defensive traits that are related to habitat use and resource acquisition. We also collected insect herbivores feeding on the plants. Our data show that sister lineages within both species complexes are more divergent in antiherbivore defences than in other non‐defensive, functional traits. Moreover, the assemblages of herbivore communities are dissimilar between the populations of coexisting I. capitata lineages. Synthesis. Our results are consistent with the idea that for the I. capitata and I. heterophylla species complexes, interactions with their natural enemies may have played a significant role in their phenotypic divergence and potentially in their diversification and coexistence. It also suggests that defensive traits are evolutionary labile.